Alcohol Production from Cassava Starch by Co-immobilized Zymomonas mobilis and Immobilized Glucoamylase - Ho, Y. C.; Mohd Ghazali, Hasanah (1986)
Simultaneous saccharification and fermentation of dextrin£zed cassava starch to glucose and alcohol, respectively, were carried out by co-immobilized Zymomonas mobilis and immobilz'zed glucoamylase (IG). Calcium alginate-entrapped cells and IG (4 : 1 ratio) gave an alcohol productivity of 0.30 glgww cellslh in a batchfermentation process. For continuous fermentation, 54.3 gil alcohol was produced at a dilution rate of 0.3Ih. 60% of the initial activity was lost within 3 days and, thereafter, the system entered a slowly decreasing phase ofalcohol production.